2017
DOI: 10.1097/mib.0000000000001153
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Health Insurance Policies Regarding Biologic Therapy Use in Inflammatory Bowel Disease

Abstract: The majority of the policies reviewed fail to adhere to the current AGA pathway recommendations for ulcerative colitis and CD. Further interventions are needed to better align policies with optimal evidence-based drug therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…The choice of which drug to add depends on disease severity, patient preference, and insurance policies. 3,63 Corticosteroids are utilized in most cases, often oral prednisone. However, in up to 15% of cases, acute severe UC develops, necessitating hospitalization and use of IV corticosteroids.…”
Section: Moderate To Severe Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…The choice of which drug to add depends on disease severity, patient preference, and insurance policies. 3,63 Corticosteroids are utilized in most cases, often oral prednisone. However, in up to 15% of cases, acute severe UC develops, necessitating hospitalization and use of IV corticosteroids.…”
Section: Moderate To Severe Diseasementioning
confidence: 99%
“…However, insurance policies often require step-therapy failures before approval of biologics, and insurance companies may also have preferred biologics that determine which agent is selected. 63 Corticosteroids. Corticosteroids are only used for the induction of remission.…”
Section: Moderate To Severe Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Despite improvement in clinical outcome, loss of response to anti‐TNF‐α Mabs remains a major concern in the management of IBD patients. Increasing evidences suggested that therapeutic drug monitoring (TDM) of anti‐TNF‐α Mabs could help to improve remission rate or mucosal healing achievement but the clinical interest of TDM of anti‐TNFα Mabs in IBD patients remains to be further demonstrated . One of the limitations lies in the absence of standardization of the analytical methods used to measure IFX plasma concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Antitumor necrosis factor (anti-TNF) agents are effective drugs for inducing and maintaining remission in IBD and its use may be associated with weight gain (7) . The interplay between obesity and IBD is complex and poorly understood.…”
Section: Introductionmentioning
confidence: 99%